SCHOOL LITERACY PROGRAM THROUGH THE CLASSROOM READING CORNER AT INPRES TOMBOLO ELEMENTARY SCHOOL IN TOMBOLOPAO GOWA - Zukhraeni; Akib, Erwin; Munirah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This article discusses the implementation of the School Literacy Program based on the stages of adaptation, development, and learning through the classroom reading corner and the supporting and inhibiting factors for the classroom reading corner utilization in the implementation of the School Literacy Program at Inpres Tombolo Elementary School. The research is qualitative research. The research was conducted at Inpres Tombolo Elementary School in Tombolopao Gowa. There were 12 informants in this research, which consist of the principal, 5 classroom teachers, 1 librarian, and 5 student trustees as representatives of each grade level. Data were collected through direct observation in the Education Unit, in-depth interviews with informants and documentation, and administrative completeness of the implementation of the School Literacy Program. The results indicate that the School Literacy Program at Inpres Tombolo Elementary School had been implemented well starting from the stages of adaptation, development, and learning by utilizing the classroom reading corner. In general, two reading strategies are applied in this research, namely silent and loud. The implementation of the School Literacy Program runs consistently in several classes during the learning from home because of the Covid-19 pandemic by utilizing digital platforms. Sources of reading materials only use the classroom reading corner and school library in the implementation of the School Literacy Program. Supporting factor of School Literacy Program implementation is frequently seen in the supporting facilities and infrastructure and variative reading materials. Conversely, the inhibiting factor can be overcome by various tricks as seen in the Principal’s Policy.